Prevalence of suicide and suicide ideation in Western Australia using linked data sources - Wood, Nerissa (Curtin University, 2013)
This study investigated the associates and prevalence of suicide ideation and suicide-related behaviour in Western Australian adults using linked data from the Health and Wellbeing Surveillance System; the Hospital Morbidity Database System; the Emergency Department Data Collection; the Mental Health Information System; and the Mortality Database. The prevalence of suicide ideation was around 5%, while suicide-related behaviour was less than 1%. Only 9% of respondents who self-reported suicide-related behaviour had an intentional self-harm hospitalisation.